Optimalisasi Rute Distribusi di Kantor Pos Berbasis Capacitated Vehicle Routing Problem Menggunakan Algoritma Genetika - Ismawati Ainol Robbi; Achmad Mufliq; Syahri Mu'min (Politeknik Harapan Bersama, 2026)
Distribution lies at the heart of logistics, as it directly dictates both operational costs and how fast customers receive their items. The Sidoarjo Branch Post Office, which manages a massive delivery network, currently struggles with inefficient routing and an uneven workload among its couriers. To tackle this, our study focuses on optimizing these delivery paths by applying the Capacitated Vehicle Routing Problem (CVRP) framework, powered by a Genetic Algorithm. We chose the Genetic Algorithm for its superior ability to navigate complex solution spaces without getting trapped in